PENGARUH LINGKUNGAN KERJA, BUDAYA ORGANISASI, DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN SWALAYAN BAHARI JAMBON PONOROGO - Rizki Yogi Noviana Putri (Jurnal AKTUAL, 2023)
This study aims to determine the effect of work environment, organizational culture and compensation on job satisfaction of employees of Swalayan Bahari Jambon Ponorogo. The method used by researchers in this study is a quantitative method. The data from this study were obtained from distributing questionnaires to respondents. Analysis using SPSS 22.00 software. The population in this study were all employees of the Jambon Bahari Supermarket, Ponorogo. The sample in this study amounted to 45 respondents using the probability sampling method using the saturated sampling technique. This study uses quantitative data types, with several data analysis methods namely validity test, reliability test, multiple linear regression test, coefficient of determination, iT test, and F test. The results of this study show 1) the work environment has a negative and not significant effect on job satisfaction, 2) organizational culture has a positive and significant effect on job satisfaction, 3) compensation has a positive and significant effect on job satisfaction, 4) work environment, organizational culture, and compensation has a positive and significant effect on job satisfaction.